Alih Kode Dan Campur Kode Dalam Kolom "Ah Tenane" Harian Solopos Edisi Mei 2014 - Mahmudi, Muri Fajar; , Prof. Dr.Abdul Ngalim, M.Hum (2016)
The purpose of this study is twofold. 1) to describe the code switching discourse "Ah ... Tenane" Solopos the May edition of 2014. 2) Describe code-mixing in the discourse of "Ah ... Tenane" Solopos May edition of 2014. This study is an analysis of phenomenal dynamic so that it can be done anytime and anywhere. This research subject is the discourse of humor "Ah ... Tenane" Solopos the May edition of 2014. The object of this study is the use of code switching and code-mixing in the discourse of "Ah ... Tenane" Solopos the May edition of 2014. The data analysis technique used is the frontier , The result showed a few things that need to be served. Results of research on the form and function of code-mixing and code switching on the rubric "Ah Tenane" in the May 2014 edition of the Daily Solopos there are two things. 1) The form of code-mixing in the rubric "Ah Tenane" in the May 2014 edition of the Daily Solopos four. The fourth form of a) word; b) the phrase; (c) the word; and (d) clause. Form of code-mixing is the most dominant form of the word because it influences the reader background assortment, both social and educational status. 2) The form of code on the rubric "Ah Tenane" in the May 2014 edition of the Daily Solopos two. a) The code switching between the Java language to ngoko wide variety of manners. b) Internal code switching between Indonesian to Javanese. Shape over most dominant code is an internal code switching between Indonesian to Java and vice versa because of the influence of cultural and linguistic background of the reader.